European Union's energy security with focus on trade in oil and gas with Russia - Apostol, Marina; Bolotov, Ilya; Smělá, Monika; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
My thesis is about the EU's energy security with a focus on trade in oil and gas with Russia. The research question of my thesis is the following- what are the impacts of trade in oil and gas with Russia on the EU's energy security? My goal is to explore the possible effects of oil and gas trade with Russia on the EU's energy security. In my methodology, I used neorealism and neoliberalism approaches, comparison, analysis, deduction, and observation so to answer my research question. My bachelor's thesis is divided into three parts. In the first chapter, I explored the term of energy security, energy legislation which is vital for ensuring and maintaining energy security, and the interconnection between energy trade and energy security. In the second chapter, I examined the EU's definition of energy security and its specifics of energy legislation, and the way how the EU treats oil and gas trade in its energy security strategy. In the last chapter, I explored how Russia can influence the EU's energy security via its oil and gas trade and what are the possible outcomes for the future of the EU. The results are that Russia is a strategic oil and gas partner to the EU which directly affects the EU's energy security. The main concern is put on the gas area due to its significance to the EU and increasing demand and consumption for the past years. Oil is still a crucial energy source to the EU and its energy security but in the following years, it may even lose its significance due to the EU's desire to promote a decarbonization strategy. The main effects of the EU's and Russian oil and gas trade are that the energy network with Russia is only expanding, the volumes of natural gas are increasing and the EU is becoming more dependent on Russia's energy supplies. Moreover, the EU does not manage to diversify its energy partners and its energy trade is still primarily focused on Russia.
The main concern for the EU's energy security should be possible Russia's desire to gain geopolitical power through its energy trade over the EU and influence its future energy strategies.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses